ANALISIS PERILAKU JUJUR SISWA DALAM PEMBELAJARAN IPA TERPADU MATERI KALOR DAN PERPINDAHANNYA DI SMP NEGERI 6 KOTA JAMBI - Situmorang, Parlindungan; Nurrahman, Arip (LPM Penalaran UNM, 2019)
This research aimed to analyzing student?s honest behavior grade VIIA and VIIB in SMP Negeri 6 Kota Jambi through integrated science learning in calor and its transfer. Data collection techniques are carried out by observation and documentation using questionnaire instruments. Data analysis in this research used descriptive statistical calculations. The result showed that student?s honest behavior grade VIIA in SMP Negeri 6 Kota Jambi through integrated science learning in calor and its transfer being in a good category, that is the percentage of 61,3%. While student?s honest behavior grade VIIB in SMP Negeri 6 Kota Jambi being in a very good category, that is the percentage of 60,0%. From all of result, it can be concluded that VIIA and VIIB grade student?s in SMP Negeri 6 Kota Jambi, have honest behavior in a very good category.